Application of elastography to diagnose adenomyosis and evaluate the degree of dysmenorrhea: a prospective observational study - Qianhui Ren; Xiangyi Dong; Ming Yuan; Xue Jiao; Hao Sun; Zangyu Pan; Xinyu Wang; Guowei Tao; Wang Guoyun (BMC, 2023)
Abstract Background To determine whether there is a correlation between stiffness measured by strain elastography and the severity of dysmenorrhea and to determine the value of elastography in evaluating severe dysmenorrhea in patients with adenomyosis. Methods The correlation between tissue stiffness and dysmenorrhea was analyzed by performing elastography on premenopausal women diagnosed with adenomyosis. Expression levels of transforming growth factor-β (TGF-β), α-smooth muscle actin (α-SMA), and protein gene product 9.5 (PGP9.5) were detected by immunohistochemistry; the correlation of TGF-β and α-SMA levels with the tissue stiffness and the degree of fibrosis was further analyzed. Also, the relationship of the PGP9.5 expression level with the tissue stiffness and degree of dysmenorrhea was determined. Results The degree of dysmenorrhea was significantly positively correlated with lesion stiffness in patients with adenomyosis but not with the uterine or lesion volume. The cutoff for the strain ratio was > 1.36 between the adenomyosis and control groups, with an area under the curve (AUC) of 0.987. For severe dysmenorrhea, the cutoff for the strain ratio was > 1.65 in patients with adenomyosis, with an AUC of 0.849. TGF-β, α-SMA, and PGP9.5 expression levels were higher in adenomyotic lesions than in the endometrium of the adenomyosis and control groups. Both TGF-β and α-SMA levels were positively correlated with the tissue stiffness and degree of fibrosis. Additionally, the expression level of PGP9.5 showed a positive correlation with the tissue stiffness and degree of dysmenorrhea. Conclusions Elastography can be used to evaluate the degree of dysmenorrhea; the greater the tissue stiffness, the greater the degree of dysmenorrhea. In addition, elastography performed well in the diagnosis of adenomyosis and the evaluation of severe dysmenorrhea in patients with adenomyosis.